2019
DOI: 10.1002/cplu.201900069
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generation of Silyl Anion Species through Si−B Bond Activation for the Concerted Nucleophilic Aromatic Substitution of Fluoroarenes

Abstract: In situ generated silyl anion species enable the concerted nucleophilic aromatic substitution of fluoroarenes. Model DFT calculations indicated that addition of a base to a silylborane would thermodynamically form a silyl borate complex and then kinetically release a silyl anion species through Si−B bond cleavage, and that the in situ generated silyl anion equivalent would further react with a fluoroarene through a concerted nucleophilic aromatic substitution pathway with an activation barrier of ca. 20 kcal/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
0
16
0
2
Order By: Relevance
“…Similarly, NaOtBu-mediated defluorosilylation of fluoroarene with Me 2 PhSi-Bpin was reported by Wang, Uchiyama, and coworkers (Scheme 141, bottom). 160 The concerted nucleophilic aromatic substitution pathway was supported by DFT calculations.…”
Section: C(sp 2 )-Si and C(sp 2 )-B Cross-couplingmentioning
confidence: 99%
“…Similarly, NaOtBu-mediated defluorosilylation of fluoroarene with Me 2 PhSi-Bpin was reported by Wang, Uchiyama, and coworkers (Scheme 141, bottom). 160 The concerted nucleophilic aromatic substitution pathway was supported by DFT calculations.…”
Section: C(sp 2 )-Si and C(sp 2 )-B Cross-couplingmentioning
confidence: 99%
“…12 An alternative method to prepare uorinated building blocks from uorobenzenes is C-F bond functionalisation. A number of non-catalysed, photo-catalysed and transition metal catalysed methods for the borylation, [13][14][15][16][17][18][19][20] magnesiation, [21][22][23][24] alumination [25][26][27][28] and silylation [29][30][31][32][33] of uorobenzenes have emerged in recent years. The advantage of these approaches is that they form new C-B, C-Mg, C-Al and C-Si bonds respectively, allowing access to main group intermediates that can be used in onwards reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In contrast, s-block silyl anions (M-SiR 3 ;M= Li, Na, K) have been invoked as intermediates in highly efficient methods for the defluorosi-lylation of sp 2 C À Fbonds of fluoroarenes and terminal sp 3 C À Fb onds of fluoroalkanes. [8][9][10][11] In related studies we,a nd others,h ave shown that main group nucleophiles are exceptional reagents for the CÀFfunctionalisation of fluoroarenes, fluoroalkenes and fluoroalkanes. [12][13][14][15][16][17] Strong M-F interactions provide al arge thermodynamic driving force for the reaction and can also play arole in determining the selectivity of which C À Fbond reacts.…”
mentioning
confidence: 88%
“…Despite the importance of this work, the reactions have low efficiency, they rely on the combination of copper(I) catalyst at modest loading (5 mol %), high temperatures (100 °C) and employ stoichiometric quantities of main group reagents (R 3 Si‐Bpin or B 2 pin 2 ; R=alkyl, pin=pinacolato) . In contrast, s‐block silyl anions (M‐SiR 3 ; M=Li, Na, K) have been invoked as intermediates in highly efficient methods for the defluorosilylation of sp 2 C−F bonds of fluoroarenes and terminal sp 3 C−F bonds of fluoroalkanes . In related studies we, and others, have shown that main group nucleophiles are exceptional reagents for the C−F functionalisation of fluoroarenes, fluoroalkenes and fluoroalkanes .…”
Section: Figurementioning
confidence: 99%